Effectiveness of influenza vaccination for preventing influenza-related complications in people with asthma: a systematic review protocol. Issue 3 (29th March 2016) - Vasileiou, Eleftheria; Sheikh, Aziz; Butler, Chris; von Wissmann, Beatrix; McMenamin, Jim; Ritchie, Lewis; Tian, Lilly; Simpson, Colin
Abstract : Introduction: Influenza vaccination is administered annually as a preventive measure against influenza infection and influenza-related complications in high-risk individuals, such as those with asthma. However, the effectiveness of influenza vaccination in people with asthma against influenza-related complications is still not well established. Methods and analysis: We will search the following databases: MEDLINE (Ovid), EMBASE (Ovid), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, Cochrane Database of Systematic Reviews (CDSR), Web of Science Core Collection, Science direct, WHO Library Information System (WHOLIS), Global Health Library and Chinese databases (CNKI, Wanfang and ChongQing VIP) from Jan 1970 to Jan 2016 for observational and experimental studies on effectiveness of influenza vaccine in people with asthma. The identification of studies will be complemented with the searching of the reference lists and citations, and contacting influenza vaccine manufacturers to identify unpublished or ongoing studies. Two reviewers will extract data and appraise the quality of each study independently. Separate meta-analyses will be undertaken for observational and experimental evidence using fixed-effect or random-effects models, as appropriate. Ethics and dissemination: Formal ethical approval is not required, as primary data will not be collected. The review will be disseminated in peer-reviewed publications and conference presentations.